1981
DOI: 10.1002/cber.19811140143
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Chemie des Bors, 1141) Eine einfache Synthese von Dibortetrabromid

Abstract: A Convenient Synthesis of Diboron TetrabromideTetramethoxydiborane(4) and boron tribromide react at ambient temperature with formation of diboron tetrabromide (yield 50%). methyl bromide and diboron trioxide.This makes B2Br4 readily accessible for further studies.Dibortetrahalogenide kdnnen eine Schlusselfunktion in der Organobor-Chemie ubernehmen, wie ihre stereospezifische cis-Addition an Acetylene und Olefine zu 1 ,2-Diborylderivaten2), die Ringoffnung von Cyclopropanen zu 1,3-Diborylpropanen?) oder die Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…The synthesis of B 2 X 4 L 2 (or [B 2 X 3 L 2 ]A) from B 2 X 4 (SMe 2 ) 2 (X=Cl, Br), room‐temperature‐stable solids, obtained in a single step and excellent yield from two commercially available reagents, B 2 (NMe 2 ) 4 and BX 3 (SMe 2 ) (Scheme f), is particularly attractive because all these compounds are potential precursors for low‐valent diboron species. Until now, the synthesis of such compounds relied on multi‐step, low‐yielding syntheses of pyrophoric and thermally unstable B 2 X 4 , also starting from commercially available B 2 (NMe 2 ) 4 . This new synthetic route also facilitates the scaleup of syntheses, thus opening up new horizons for reactivity studies on these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of B 2 X 4 L 2 (or [B 2 X 3 L 2 ]A) from B 2 X 4 (SMe 2 ) 2 (X=Cl, Br), room‐temperature‐stable solids, obtained in a single step and excellent yield from two commercially available reagents, B 2 (NMe 2 ) 4 and BX 3 (SMe 2 ) (Scheme f), is particularly attractive because all these compounds are potential precursors for low‐valent diboron species. Until now, the synthesis of such compounds relied on multi‐step, low‐yielding syntheses of pyrophoric and thermally unstable B 2 X 4 , also starting from commercially available B 2 (NMe 2 ) 4 . This new synthetic route also facilitates the scaleup of syntheses, thus opening up new horizons for reactivity studies on these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…catecholate or pinacolate) are not directly involved. Very recently,B raunschweig et al reported the convenient synthesis of the tetrahalo-diboranes B 2 Cl 4 (previously generally prepared in as pecial high-vacuuma pparatus by co-condensation of copper metal atoms with BCl 3 ), [2] B 2 Br 4 (accordingt oa procedure of Nçth et al) [3] and B 2 I 4 , [4] and studied reactions proceeding under retention of the BÀBb ond. [5] Most studies concentrate on diborane(4) compoundsw ith sp 2 -hybridized boron atoms.T hey can be regarded as boryl-substituted boranes that react as electrophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Most studies concentrate on diborane(4) compoundsw ith sp 2 -hybridized boron atoms.T hey can be regarded as boryl-substituted boranes that react as electrophiles. Lately severals pectacular results were reported with sp 3 -sp 3 -hybridized diborane(4) and also sp 3 -sp 3 -diborane(6) derivatives, [6][7][8][9][10][11][12][13][14][15][16] but nevertheless their chemistry is still underdeveloped. Braunschweig et al used a biscarbene-stabilized tetrabromo-diborane(4) for reduction to give the first compoundwith aB Bt riple bond.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations